2022
DOI: 10.3390/ma15062155
|View full text |Cite
|
Sign up to set email alerts
|

Porous Coatings to Control Release Rates of Essential Oils to Generate an Atmosphere with Botanical Actives

Abstract: Essential oils have been used in diverse areas such as packaging, agriculture and cosmetics, for their antimicrobial and pesticide activity. The organic volatile compounds of the essential oils are involved in its activity. Controlling their release helps to prolong their functionality. In this study, a functionalized calcium carbonate porous coating was employed to control the release of thyme and rosemary oil in a confined space. The release rate was evaluated at 7 °C and 23 °C, gravimetrically. It was shown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
1
2
0
Order By: Relevance
“…This phenomenon, along with the antibacterial mechanism of menthol, requires a deeper investigation. Apart from the MEO effects on the viability of S. typhimurium cells, our results are consistent with the general principle that more EO evaporates at higher temperatures; thus, the killing of bacteria is faster at higher temperatures [55]. However, the actions of EOs are not always predictable, even based on the boiling temperatures of the components; the mechanisms of EOs are more complicated and still require elucidation [16].…”
Section: Effects Of Meo and Ceo Vapors On The Viability Of S Typhimur...supporting
confidence: 84%
“…This phenomenon, along with the antibacterial mechanism of menthol, requires a deeper investigation. Apart from the MEO effects on the viability of S. typhimurium cells, our results are consistent with the general principle that more EO evaporates at higher temperatures; thus, the killing of bacteria is faster at higher temperatures [55]. However, the actions of EOs are not always predictable, even based on the boiling temperatures of the components; the mechanisms of EOs are more complicated and still require elucidation [16].…”
Section: Effects Of Meo and Ceo Vapors On The Viability Of S Typhimur...supporting
confidence: 84%
“…For example, Milićević et al [ 67 ] indicated that zeolite adsorbs the droplets of clove bud essential oil due to its porosity; the insecticidal, antifungal, and antibacterial effects of essential oils were augmented by loading in this porous material. In a study by Hettmann et al [ 68 ], a functionalized calcium carbonate porous coating was used for controlled release of rosemary and thyme essential oil. The authors found that thyme essential oil required almost double the time required by rosemary essential oil to reach the saturation point, which can be explained by diverse chemical composition and concentration of monoterpenes between the two essential oils.…”
Section: Discussionmentioning
confidence: 99%
“…Essential oil evaporates from the pores of porous materials and distributes to the air. The study by Hettmann et al [ 68 ] mainly focused on physical influences, including degrees of loading and temperature, on release of essential oils from porous materials.…”
Section: Discussionmentioning
confidence: 99%